2015
DOI: 10.1155/2015/601985
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy and Roux-en-Y Gastric Bypass Alter the Gut-Brain Communication

Abstract: This study investigated the anatomical integrity of vagal innervation of the gastrointestinal tract following vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) operations. The retrograde tracer fast blue (FB) was injected into the stomach to label vagal neurons originating from nodose ganglion (NG) and dorsal motor nucleus of the vagus (DMV). Microglia activation was determined by quantifying changes in the fluorescent staining of hindbrain sections against an ionizing calcium adapter bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 63 publications
1
51
0
Order By: Relevance
“…Similar to vagotomy, it is possible that inflammation-mediated damage to the gastric vagus system may reduce food intake and increase satiety signaling in these animals [62, 63]. Consumption of HF, highly palatable food in rodents has been shown to promote hyperphagia.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to vagotomy, it is possible that inflammation-mediated damage to the gastric vagus system may reduce food intake and increase satiety signaling in these animals [62, 63]. Consumption of HF, highly palatable food in rodents has been shown to promote hyperphagia.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the density may reflect a sprouting of vagal inputs into the hindbrain feeding centers. Interestingly, our previous studies revealed that damage to peripheral axons of the vagus (subdiaphragmatic vagotomy) also induced transient decrease in the density of vagal afferents projecting to the NTS (Ballsmider et al 2015, Peters et al 2013) followed by vagal inputs sprouting. Vagal damage also resulted in microglia activation in the NTS and DMV (Gallaher et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Recent rodent studies indicate that major neuronal reorganization takes place in lower brainstem after bariatric interventions (Ballsmider et al, 2015). Future research may reveal novel pathways linking brainstem function to duodenal-sensitive dopamine cells.…”
Section: Discussionmentioning
confidence: 99%